Improving Children's Digital Literacy: A Quantitative Study on the Use of Digital Storybooks in Elementary Schools - Firsta Novia Nurhidayah; Setiawan Edi Wibowo (Jurnal Ilmiah Sekolah Dasar, 2025)
Students in elementary school are in a crucial phase of development, where they are beginning to be exposed to various types of digital media. In this phase, it is important to introduce learning media that can motivate students to improve their digital literacy skills. One of the learning media is digital storybooks. Digital storybooks have a more attractive appearance when compared to printed storybooks. The purpose of this study is to determine the influence of digital storybooks on the digital literacy of students in elementary schools. The method used in this study is a quasi-experiment with a non-equivalent control group design. The research sample consisted of 90 students in grade IV of elementary school. The experimental group in this study used a digital storybook, while the control group used a printed storybook. The data collection technique uses a test in the form of multiple-choice questions. Data analysis was carried out using descriptive analysis techniques and the Independent Sample t-test test. The results of the hypothesis test using the Independent Sample t-test showed a significance value of 0.000 (<0.05), meaning that students in the experimental class who were treated using digital storybooks had better digital literacy skills than students in the control class who used printed storybooks. So, it can be concluded that digital storybooks have an effect on the digital literacy of students in elementary school.